2019
DOI: 10.3390/cells8111374
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Prevents Cartilage Degradation: A Metabolomics Study Pinpoints the Involvement of Vitamin B6

Abstract: Osteoarthritis (OA) is predominantly characterized by the progressive degradation of articular cartilage, the connective tissue produced by chondrocytes, due to an imbalance between anabolic and catabolic processes. In addition, physical activity (PA) is recognized as an important tool for counteracting OA. To evaluate PA effects on the chondrocyte lineage, we analyzed the expression of SOX9, COL2A1, and COMP in circulating progenitor cells following a half marathon (HM) performance. Therefore, we studied in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Finally, although it is known that the absorption of B group vitamins like niacin and riboflavin is reduced by psychological factors, stress, and the use of sleeping-inducing drugs (which is common in FMS patients) [51], there are no studies in the literature about the efficacy of these supplementations in fibromyalgia patients. On the other hand, a recent study suggests the potential relationship between physical activity and vitamin B6 levels in the prevention of inflammatory articular processes [52]. Physical activity and vitamin B supplementation could be considered synergic approaches in the prevention of pain and potential inflammatory processes.…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…Finally, although it is known that the absorption of B group vitamins like niacin and riboflavin is reduced by psychological factors, stress, and the use of sleeping-inducing drugs (which is common in FMS patients) [51], there are no studies in the literature about the efficacy of these supplementations in fibromyalgia patients. On the other hand, a recent study suggests the potential relationship between physical activity and vitamin B6 levels in the prevention of inflammatory articular processes [52]. Physical activity and vitamin B supplementation could be considered synergic approaches in the prevention of pain and potential inflammatory processes.…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…As vitamin B6 cannot be produced by mammals, it may be introduced in the intestine only through the diet or by symbiotic bacteria [86]. Therefore, we have suggested that increased levels of vitamin B6 might be due to the physical performance [85]. This finding is intriguing in consideration of vitamin B6 role in diabetes, a disease frequently associated to obesity.…”
Section: Physical Exercise and Changes In Gut Microbiota In Obese Indmentioning
confidence: 89%
“…In the gut several bacteria synthesize vitamins such as vitamin K, folic acid or thiamine [80]. Recently, we found that exercise increased the levels of two metabolites of vitamin B6 salvage pathway (pyridoxal 5 -phosphate, pyridoxamine 5 -phosphate) [85]. As vitamin B6 cannot be produced by mammals, it may be introduced in the intestine only through the diet or by symbiotic bacteria [86].…”
Section: Physical Exercise and Changes In Gut Microbiota In Obese Indmentioning
confidence: 99%
“…Cell viability was evaluated by using the Cell proliferation kit II (XTT Chemicon) as previously described [ 26 ]. Six replicates in three independent experiments were tested.…”
Section: Methodsmentioning
confidence: 99%